INTERAKSI EDUKATIF DALAM PEMBELAJARAN PAI - Pajar Anwar (BRIGHT VISION Journal of Language and Education, 2022)
This paper wants to describe the educational interaction in PAI learning. This study uses a descriptive qualitative approach by collecting data from various relevant written sources. The results of the author's search show that the ongoing learning process does not escape the interaction between teachers as educators and students. This interaction is nothing but a form of communication of teachers as informers and students as recipients of messages, with the help of media and channels that have been planned by educators. This interaction is called educational interaction. Educative interaction, especially in PAI learning, occurs in the learning process carried out by educators with several principles, as follows: learning objectives, learning materials, teaching and learning activities, learning methods, media, learning resources and evaluation.Keywords: Interaction, Educational, PAI